Peningkatan Pemahaman Bangun Ruang Melalui Metode Team Teaching dengan Penggunaan Alat Peraga Pada Siswa Kelas 1 MI Jami'atul Ulum Tahun Ajaran 2024/2025 (Al Irfan : Jurnal Ilmu Pendidikan dan Penelitian, 2025)
This study aims to improve the understanding of grade 1 students of MI Jami'atul Ulum about spatial figures using the team teaching method and the use of teaching aids. Students in this class have diverse characteristics, including some students who are very active, noisy, naughty and have not been able to read and write. This study was conducted in two cycles using various teaching aids, such as concrete objects, toothpicks, satay skewers, plasticine, spinning wheels, and block space boards. The results showed that in the pre-cycle, 16 students (57%) completed and 12 students (43%) had not completed with an average score of 68.6. After the action, the pre-test showed an increase with 18 students (64%) completing and 10 students (36%) having not completed, with an average score of 73.6. In the post-test, 24 students (86%) managed to achieve the KKM and only 4 students (14%) had not completed, with an average score of 79.8. This study shows that the team teaching method with teaching aids is effective in improving the understanding of spatial figures in grade 1 students of MI Jami'atul Ulum.